Filozofia arabska, islamska czy muzułmańska? Kilka uwag terminologicznych - Kokoć, Damian (Humaniora. Czasopismo Internetowe, 2021)
There is no agreement among the students of the works of Al-Fārābī, Avicenna and Averroes on how their philosophy should be named. The following terms are most frequently used: Muslim philosophy, Arab philosophy, and Islamic philosophy. A closer look at the arguments of the supporters of each of these choices shows that the reason for those terminological discrepancies depends on the postulated relation between religion and philosophy, or more broadly, between religion and science. We emphasize either the ethnic aspect (Arab) or the dominant culture-forming factor (Islam) depending on the terminology chosen. This article aims to present and analyze the arguments of the supporters of each of the terms. The author focuses on philosophers living in the Middle Ages. The question of which of the aforementioned terms best represents the phenomenon in focus will be seen when we study those terms by putting them together in two pairs: the first, Arab philosophy – Muslim philosophy, and the second, Muslim philosophy – Islamic philosophy.